Phytoplankton species diversity and abundance in the near shore waters of Tanzanian side of Lake Victoria - Mbonde, ASE; Shayo, S; Sekadende, BC; Lyimo, TJ (Tanzania Journal of Science, 2021)
The survey was carried out in January/February and July/August 2002 to investigate phytoplankton species diversity, spatial distribution, numerical abundance and total biomass (chlorophyll a concentration) in 10 selected stations on the Tanzanian side of Lake Victoria. At each station, samples for diversity data were collected by plankton net, which was towed at the surface water, while those for spatial distribution and abundance were collected using a 1 l Van Dorn water sampler. A total of 113 species belonging to 52 different genera were identified. Cyanobacteria were the most diverse group in both seasons. The concentration of chlorophyll a ranged from below 0.1 µg/l recorded at Mwanza Gulf to 14.52 µg/l at Bulamba station. The phytoplankton abundance ranged from 245 cells/ml recorded at Baumann's Gulf to 77 cells/ml at Lamadi during January/February sampling; and from 1519 to 276 cells/ml at Bulamba and Mwanza Gulf respectively, during the July/August sampling. Highest numerical abundance was recorded in Mara zone in both samplings. Cyanobacteria species had higher percentage composition, constituting up to 35% and 41% of all identified individuals during January/February and July/August, respectively.